Homozygous losses detected by array comparative genomic hybridization in multiplex urothelial carcinomas of the bladder - Beöthe, Tamás; Zubakov, Dmitry; Kovacs, Gyula (Cancer genetics, 2015)
Urothelial carcinomas (UCs) may present at first as a solitary or multifocal neoplasm. We applied high resolution array comparative genomic hybridization to 24 solitary and 32 multiplex UCs and used the hidden Markov model algorithm to identify the copy number changes at the probe level. Copy number losses and homozygous deletions at the chromosome 9p region affecting the CDKN2A and MTAP genes were the most frequent alterations in both groups of tumors. We have delineated two new tumor suppressor gene regions at chromosome 9p that harbor the PTPRD and BNC2 genes. Copy number losses at chromosomal regions 2q, 8p, and 18p occurred preferentially in solitary UCs, whereas multiplex UCs displayed loss of large chromosomal regions at 9q, 10q, 11q, 18q, and 21q. Homozygous deletions harboring loci of cell adhesion genes such as claudins, desmocollins, and desmogleins were seen exclusively in multiplex UCs. Amplifications occurred only in invasive G3 UCs irrespective of staging. Our study suggests that solitary and multiplex UCs may have divergent genetic pathways. The biallelic inactivation of cellular adhesion genes by homozygous deletions in multiplex UCs may explain the frequent intravesical spreading of tumor cells.
Gesehen am 20.05.2020